The role of conditioning on performance in professional soccer - Reer, R.; Stein, D.; Wellmann, K.; Braumann, K. M. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Expert suggest that since 1990`s there has been a steady increase in performance demand as well as performance level in professional soccer players. The endurance conditioning level of the German national players in the 1990`s is similar to the conditioning of the 3rd division players today. In contrast to endurance performance, the sprint performance level of the national players in the 1990`s is achieved only in the 1st professional soccer division today. Therefore, the aim of this study was, based on multiyear record keeping, data collection, and observations, to investigate how the sport specific endurance, speed, and strength that are prerequisites for successful professional soccer players can be improved, maintained, and enhanced. Methods: We conducted numerous seasonal tests with a group of professional soccer players. The tests were soccer specific endurance, sprints, jumps and strength training of specific muscle groups. In addition to soccer specific demands, we designed and implemented individually tailored strength and interval training. This type of training was conducted 3-4 hours per week. Results: There were statistically significant improvements in soccer specific endurance from the beginning of the 3rd division 4.11+0.19 m/s to 4.26+0.2 (p<0.01) at entry to 2nd division and improved to 4.62+0.25 m/s (p<0.001) at the start of the 1st division. Similar results were observed for 30m sprints. They improved their sprint performance time from the beginning of the 3rd division to 2nd division from 4.27+0.23s to 4.1+0.14s (p<0.01). At entry to 1st division they improved their sprint time to 4.0+0.15s (p<0.001). However, there was no significant difference for counter movement jumps (38.0±3.5cm to 39.2±4.2cm). Discussion: The performance of a professional soccer team depends on multitude of factors. The results suggest that systematic and individualized improvements in soccer specific endurance and sprint performance greatly contribute to the success in professional soccer. In addition, our results suggest that players possess physiological abilities that can be harvested and thus can greatly benefit individually and collectively from training methods employed in this investigation.